Sikap dan pengetahuan Mahasiswa Fakultas Sains dan Teknologi UIN Walisongo Semarang terhadap limbah pangan (food waste) - Chilma Chairani; Siti Ropiah; Ahmad Fauzan Hidayatullah (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2023)
Waste is a complex problem in communities that do not care about the environment. One of the serious problems experienced by many countries, both developed and developing is Food Waste. Therefore, practical solutions are needed to overcome this phenomenon. This research uses literature study methods and case studies by involving students from the Faculty of Science and Technology UIN Walisongo Semarang as respondents to questionnaires related to Food Waste. Based on the results of the research, the attitude of students of the Faculty of Science and Technology regarding Food Waste is that most are aware of the importance of managing food waste properly so that it does not have a damaging impact on the environment. Meanwhile, the knowledge of students from the Faculty of Science and Technology is that many of them already know information related to Food Waste, the causes and impacts arising from this food waste. The results of the questionnaire to 53 respondents obtained 58.5% results in Biology Education Study Program, 18.9% Mathematics Education Study Program, 9.4% Chemistry Education Study Program, 5.7% Pure Mathematics, 3.8% Pure Chemistry, 1.9% Study Program Pure Chemistry and Pure Biology.